2017
DOI: 10.3892/br.2017.926
|View full text |Cite
|
Sign up to set email alerts
|

Development of gene polymorphisms in meditators of nonalcoholic fatty liver disease

Abstract: Abstract. Nonalcoholic fatty liver disease (NAFLD) is the most prevalent liver disease worldwide, the morbidity of which closely correlates with diversity of ethnicity, minority, family and location. Its histology spans from simple steatosis, to nonalcoholic steatohepatitis, which ultimately results in fibrosis, cirrhosis and hepatocellular carcinoma. The accelerating prevalence of NAFLD is due to an incremental incidence of metabolic syndrome that is distinguished by dyslipidemia, glucose impairment, obesity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 81 publications
(85 reference statements)
0
5
0
2
Order By: Relevance
“…Excessive CYP2E1 activation in perivenular hepatocytes causes an increase in the area of hepatocyte damage, at least in CYP2E1 transgenic murine models. In particular, the variant CYP4502E1*5B (RsaI, −1053C>T) seems to increase the enzyme transcription and activity, resulting in an increase in the ROS production in alcoholic cirrhotic patients, but evidence is not yet available for NAFLD patients [369].…”
Section: Other Genetic Variantsmentioning
confidence: 99%
“…Excessive CYP2E1 activation in perivenular hepatocytes causes an increase in the area of hepatocyte damage, at least in CYP2E1 transgenic murine models. In particular, the variant CYP4502E1*5B (RsaI, −1053C>T) seems to increase the enzyme transcription and activity, resulting in an increase in the ROS production in alcoholic cirrhotic patients, but evidence is not yet available for NAFLD patients [369].…”
Section: Other Genetic Variantsmentioning
confidence: 99%
“…[ 6 ] According to the present data, NAFLD affects 10%–30% of the general population in various countries, which has been viewed as a huge global health burden. [ 7 , 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[6] According to the present data, NAFLD affects 10%-30% of the general population in various countries, which has been viewed as a huge global health burden. [7,8] Little is known about the latent mechanism involved in the development and pathogenesis of NAFLD, and yet it is a complicated metabolic process in which both environmental and genetic factors are etiology. [9] At present, genome-wide association studies (GWAS) have demonstrated several conspicuous genetic susceptibility genes such as PNPLA3, SAMM50, PARVB, APOC3, PPAR-γ, NCANCILP2, FABP1, AGTR1, GSTs, which had been verified the crucial roles in the disease onset and progression of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Другая мутация в гене TM6SF2, кодирующем трансмембранный белок 6 суперсемейства-2, способствующая задержке триглицеридов и холестерина в печени, с одной стороны, предрасполагает к НАЖБП и фиброзу печени, с другой -обладает кардиопротективными эффектами за счет снижения уровня секреции ЛПОНП и концентрации триглицеридов в сыворотке крови [41]. Данные ряда исследований свидетельствуют, что мутации генов, кодирующих рецепторы адипонектина и лептина, связаны не только с более тяжелым поражением печени, но и с выраженными метаболическими нарушениями (дислипидемия, сахарный диабет), предрасполагающими к развитию и прогрессированию сердечно-сосудистых заболеваний [42,43].…”
unclassified